Physical and mechanical properties of wood of plantation grown Albizia lebbeck in the savannah ecological zone, Ghana - Tampori, Enoch Gbapenuo (Les (Ljubljana), 2024)
The increasing scarcity of major commercial tropical hardwood species has necessitated the utilization of plantation grown exotic timber species as a potential means of maintaining Ghana’s foundation of timber resources. To better consider Albizia lebbeck as a substitute for wood species which are being seriously over-exploited to the point of commercial extinction, its wood properties were characterized to expatiate its utilization potentials. Three mature plantation grown Albizia lebbeck trees with diameters 45-50 cm at breast height were purposively selected and sampled at four stem height levels of tree height. The samples were sawn into the required sizes in accordance with the British standard, BS 373 (1957) for testing. The heartwood and sapwood proportions were evaluated and the samples were examined for hardness, bending strength (MOE and MOR), compression strength parallel to grain, shear strength parallel to grain, and air-dry density. All treeshad a significantly higher heartwood than sapwood percentage. The air-dry density values at 12% MC were 868 kg/m3, 806 kg/m3, 695 kg/m3 and 564 kg/m3 for four sections of the stem (heights 0-25%, 26-50%, 51-75% and 76-100%).In general, the plantation grown Albizia lebbeckex hibited favourable strength values, suggesting that it is endowed with adequate properties for being an alternative species to supply the wood industry.
Keywords: Albizia lebbeck; beljava; gostota lesa; heartwood; jedrovina; lesser-known timber species; manj znane lesne vrste; modul elastičnosti; modulus of elasticity; modulus of rupture; plantation; plantaže; sapwood; upogibna trdnost; wood density